Preparation and Characterization of Flurbiprofen/β-Cyclodextrin Inclusion Complex - Thi Thanh Binh, Nguyen; Thi Quynh Xuan, Ho; Thi Hai Yen, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 3, 2020)
This study aims to ameliorate the water solubility of flurbiprofen by using β -cyclodextrin ( β -CD). The drug/ligand 1:1 (M/M) stoichiometry was determined based on the effect of β -CD on the solubility of flurbiprofen. Several methods of preparing flurbiprofen/ β -CD inclusion complex were investigated and a solvent method using hot water to dissolve the starting materials was selected. The selected method showed a lot of advantages such as high complexing ability, good product yield, simple and eco-friendly process. The obtained product was characterized using various analytical techniques such as high-performance liquid chromatography, differential scanning calorimetry, Fourier transform infrared spectroscopy, X-ray diffraction and scanning electron microscopy. The product had a predominantly amorphous form with clathrate particles of about 2-7 µm in size, irregular edges and rough surfaces. The study results show that in the complexing process, flurbiprofen replaced water molecules located in the conical cavity of β -CD. The complex contained 19.91% flurbiprofen by mass with water solubility at 37°C was 1,100 µg/ml. The results also show that the complexing with β -CD significantly improved the water solubility of flurbiprofen by both speed and level. Keywords Flurbiprofen, β -cyclodextrin, inclusion complex, water solubility, preparation, characterization. References [1] K. Maroof, F. Zafar, H. Ali, S. Naveed, Flurbiprofen: a potent pain reliever, J. Bioequiv. Availab. 7(1) (2015) 056-058. https://doi.org/10.4172/jbb.1000214. [2] J.J. Thebault, G. Lagrue, C.E. Blatrix, L. Cheynier, R. Cluzan, Clinical pharmacology of flurbiprofen: a novel inhibitor of platelet aggregation, Curr. Med. Res. Opin. 5(1) (1977) 130-134. https://doi.org/10.1185/03007997709108990. [3] H. Geerts, Drug evaluation: (R)-flurbiprofen - an enantiomer of flurbiprofen for the treatment of Alzheimer's disease, Idrugs. 10(2) (2007) 121-133. [4] P.L. McGeer, M. Schulzer, E.G. McGeer, Arthritis and anti-inflammatory agents as possible protective factors for Alzheimer's disease: a review of 17 epidemiologic studies, Neurology. 47(2) (1996) 425-432. https://doi.org/10.1212/WNL.47.2.425. [5] S. Meister, I. Zlatev, J. Stab, D. Docter, S. Baches, et al., Nanoparticulate flurbiprofen reduces amyloid-β 42 generation in an in vitro blood-brain barrier model, Alzheimers Res. Ther. 5(6) (2013) 51-63. https://doi.org/10.1186/alzrt225. [6] K.P. Townsend, D. Praticò, Novel therapeutic opportunities for Alzheimer’s disease: focus on nonsteroidal anti-inflammatory drugs, FASEB J. 19(12) (2005) 1592-1601. https://doi.org/10.1096/fj.04-3620rev. [7] C.K. Kim, Y.S. Yoon, J.Y. Kong, Preparation and evaluation of flurbiprofen dry elixir as a novel dosage form using a spray-drying technique, Int. J. Pharm. 120 (1995) 21-31. https://doi.org/10.1016/0378-5173(94)00375-F. [8] M.J. Habib, M.T. Phan, G. Owusu-Ababio, Dissolution profiles of flurbiprofen in phospholipid solid dispersions, Drug Dev. Ind. Pharm. 24 (1998) 1077-1082. https://doi.org/10.3109/03639049809089952. [9] D.H. Oh, Y.J. Park, J.H. Kang, C.S. Yong, H.G. Choi, Physicochemical characterization and in vivo evaluation of flurbiprofen-loaded solid dispersion without crystalline change, Drug. Deliv. 18 (2010) 46-53. https://doi.org/10.3109/10717544.2010.509365. [10] G.D. Gupta, S. Jain, N.K. Jain, Formulation of an aqueous injection of flurbiprofen, Pharmazie. 52 (1997) 709-712. https://doi.org/10.1080/10826079708005547. [11] K.W. Ambade, S.L. Jadhav, M.N. Gambhire, S.D. Kurmi, V.J. Kadam, K.R. Jadhav, Formulation and evaluation of flurbiprofen microemulsion, Curr. Drug Deliv. 5 (2008) 32–41 [12] H.H. Baek, S.Y. Kwon, S.J. Rho, W.S. Lee, H.J. Yang, J.M. Hah, H.G. Choi, Y.R. Kim, C.S. Yong, Enhanced solubility and bioavailability of flurbiprofen by cycloamylose, Arch. Pharm. Res. 34 (2011) 391-397. https://doi.org/10.1007/s12272-011-0306-x. [13] A. Muraoka, T. Tokumura, Y. Machida, Evaluation of the bioavailability of flurbiprofen and its β-cyclodextrin inclusion complex in four different doses upon oral administration to rats, Eur. J. Pharm. Biopharm. 58(3) (2004) 667-671. https://doi.org/10.1016/j.ejpb.2004.03.030. [14] T. Tokumura, A. Muraoka, Y. Machida, Improvement of oral bioavailability of flurbiprofen from flurbiprofen/beta-cyclodextrin inclusion complex by action of cinnarizine, Eur. J. Pharm. Biopharm. 73 (2009) 202-204. https://doi.org/10.1016/j.ejpb.2009.04.018. [15] D. Li, M. Han, P. Balakrishnan, Y. Yan, D. Oh, et al., Enhanced oral bioavailability of flurbiprofen by combined use of micelle solution and inclusion compound, Arch. Pharm. Res. 33(1) (2010) 95-101. https://doi.org/10.1007/s12272-010-2231-9. [16] H. Arima, K. Motoyama, T. Irie, Recent findings on safety profiles of cyclodextrins, cyclodextrin conjugates, and polypseudorotaxanes, in: E. Bilensoy (Ed.), Cyclodextrins in Pharmaceutics, Cosmetics, and Biomedicine: Current and Future Industrial Applications, John Wiley & Sons Inc., Hoboken, 2011, pp. 91-122. https://doi.org/10.1002/9780470926819.ch5. [17] T.J. Grattan, Inclusion complexes of beta-cyclodextrin with flurbiprofen, ketoprofen and naproxen, International patent WO1995007104A1, March 16, 1995. [18] M. Cirri, C. Rangoni, F. Maestrelli, G. Corti, P. Mura, Development of fast-dissolving tablets of flurbiprofen-cyclodextrin complexes, Drug Dev. Ind. Pharm. 31(7) (2005) 697-707. https://doi.org/10.1080/03639040500253694. [19] M. Tirunagari, N. Mehveen, M.F. Qureshi, J.P. Sultana, V. Tirunagari (2012), Solubility Enhancement of Flurbiprofen using Different Solubilization Techniques, Int. J. Pharm. Pharm. Sci. 4(4) (2012) 97-100. [20] P. Saokham, C. Muankaew, P. Jansook, T. Loftsson, Solubility of cyclodextrins and drug/cyclodextrin complexes, Molecules. 23(5) (2018) 1161-1175. https://doi.org/10.3390/molecules23051161. [21] S. Pereva, T. Sarafska, S. Bogdanova, T. Spassov, Efficiency of “cyclodextrin-ibuprofen” inclusion complex formation, J. Drug Deliv. Sci. Tec. 35 (2016) 34-39. https://doi.org/10.1016/j.jddst.2016.04.006. [22] T.T.B. Nguyen, N.A. Dang, M.A. Tran, T.H. Nguyen, Validation of a high-performance liquid chromatographic method with diod array detection for the quantification of flurbiprofen in 100 mg film-coated tablet, VNU Journal of Science: Medical and Pharmaceutical Sciences. 33(2) (2017) 41-49. https://doi.org/10.25073/2588-1132/vnumps.4085. [23] T. Higuchi, K.A. Connors, Phase-solubility techniques, Adv. Anal. Chem. Instrum. 4 (1965) 117-122.